2022
DOI: 10.1080/21645698.2021.2015272
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of information channel on the relationship between type of information search and knowledge of genetically modified organisms

Abstract: This study explores how the type of information search and information channel can influence the objective knowledge of consumers on genetically modified organisms. We divided the types of information search on genetically modified organisms into active and passive seekers, and then examined how their knowledge differed depending on preferred the information channel (i.e., government, portals, non-government organization (NGO) sites). An online survey was conducted with Korean men and women aged 19 or older. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Despite passing 20 years since the first transgenic products were introduced in Iran and tense debates at the policy-making and media levels have proceeded, Tehranian are not familiar with the GMO term. According to others conducted research over the last 40 years, some other researchers also reported limited consumer knowledge of GMOs [ [34] , [35] , [36] ]. In addition, several previous studies have shown that the majority of consumers just have heard the name of G.M.…”
Section: Discussionmentioning
confidence: 99%
“…Despite passing 20 years since the first transgenic products were introduced in Iran and tense debates at the policy-making and media levels have proceeded, Tehranian are not familiar with the GMO term. According to others conducted research over the last 40 years, some other researchers also reported limited consumer knowledge of GMOs [ [34] , [35] , [36] ]. In addition, several previous studies have shown that the majority of consumers just have heard the name of G.M.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the authority is quite important due to credibility (Freeman et al , 2020; Johnson, 2018; Metzger et al , 2010; Niedringhaus, 2018), and it seems that students considered it when the content was given in their own native language regardless of the content type (academic vs non-academic). When the language changes to English, then only the appearance criterion appears as the one mutual criterion because the use of language in online sources can give clues about the quality of the source, and thus, they approach sceptically (Kohnen et al , 2022; Nam and Lee, 2022). In terms of content (academic vs non-academic), appearance was the most used criterion for academic content, which is in line with Sendurur’s (2018) findings, but currency was the least used criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Certain strategies might let the searchers access credible information. Being sceptical, a rule follower, a rigid thinker, rational and information conscious are recently reported strategies in the literature (Kohnen et al , 2022; Nam and Lee, 2022). How to interact with SERPs or how to adapt strategies depends on various factors, including domain knowledge (Wineburg and McGrew, 2017), task difficulty (Agarwal et al , 2011), task type (Kim et al , 2021; Sendurur, 2018), rank of presented information (Schultheiß et al , 2018), reputation of source (Unkel and Haas, 2017), familiarity (Hinostroza et al , 2018; Hsu, 2014; Steichen and Lowe, 2021) and language (Chu et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous research on food labeling was limited to individual labeling systems, such as genetically modified food (Hwang & Nam, 2021;Nam & Lee, 2022), health supplements (Moss, 2006;Vincent, 2017), and nutrition labeling (Brecher et al, 2000;Wang et al, 1995). This study, however, is not limited to analyzing consumers' perceptions and characteristics of individual specific food labels but instead examines differences in consumers' perceptions of the overall food labeling system.…”
Section: Food Labelingmentioning
confidence: 99%